Development of a specific tool for measuring safety climate in the furniture industry - Rodrigues, Matilde (2012)
The furniture industry represents a significant impact in the Portuguese economy. However, it is a sector that has a reduced professionalization in terms of management, marketing and trade policies, and with low qualification and undifferentiated workers. Besides, the number of work accidents in this industry sector is also high. This high number of accidents is a consequence of several factors, namely the specific risk of the sector, the stakeholders’ low safety concerns, the lack of machine maintenance, and lower workers qualification.